2013
DOI: 10.1097/phm.0b013e31829b4bd8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a New Ultrasound Approach with Electrodiagnostic Studies to Confirm Clinically Defined Carpal Tunnel Syndrome

Abstract: US cannot replace EDX for confirmation of clinical diagnosis of CTS. However, an abnormal US test result has a high positive predictive value for abnormal EDX result in clinically defined CTS. US might reveal relevant anatomic information preoperatively that rarely has a direct influence on treatment management of patients with CTS. US testing, taking morphometric data into account, does not have the same diagnostic value as EDX does in confirming CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 16 publications
1
35
0
3
Order By: Relevance
“…17 In early stages, these morphologic changes may exist before the nerve damage occurs that can be picked up by electrodiagnostic evaluations. 18,19 Once physiological changes progress beyond electrodiagnostic thresholds, the continued increase in CSA has been correlated positively with severity classification. 8,20 Similarly, intraneural vascularity may be useful for identifying stages and severity of CTS.…”
Section: Introductionmentioning
confidence: 99%
“…17 In early stages, these morphologic changes may exist before the nerve damage occurs that can be picked up by electrodiagnostic evaluations. 18,19 Once physiological changes progress beyond electrodiagnostic thresholds, the continued increase in CSA has been correlated positively with severity classification. 8,20 Similarly, intraneural vascularity may be useful for identifying stages and severity of CTS.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐sectional area measurement is a well‐established method, and the results of this study showed that the patients with acromegaly had an increased cross‐sectional area compared with the healthy control group, which provides an insight into median nerve morphologic characteristics. Lack of electrodiagnostic testing might be considered a limitation of this study, although electromyographic findings have previously been reported to be correlated with US findings …”
Section: Discussionmentioning
confidence: 90%
“…At present, CTS patients associated with ulnar nerve involvement do not receive sufficient attention. Nevertheless, a neurophysiological approach is the most sensitive method for evaluating peripheral nerve compression damage (Claes et al, 2013). In the present study, we classified the CTS severity of all patients including those with and without fifth digit symptoms by using neurophysiological methods.…”
Section: Discussionmentioning
confidence: 99%